2019
DOI: 10.1016/j.ebiom.2018.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Senolytics in idiopathic pulmonary fibrosis: Results from a first-in-human, open-label, pilot study

Abstract: Background: Cellular senescence is a key mechanism that drives age-related diseases, but has yet to be targeted therapeutically in humans. Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal cellular senescenceassociated disease. Selectively ablating senescent cells using dasatinib plus quercetin (DQ) alleviates IPF-related dysfunction in bleomycin-administered mice. Methods: A two-center, open-label study of intermittent DQ (D:100 mg/day, Q:1250 mg/day, three-days/week over three-weeks) was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
599
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 838 publications
(657 citation statements)
references
References 59 publications
8
599
0
5
Order By: Relevance
“…The critical role for AT2 senescence in both initiation and progression of fibrosis was suggested by progressive fibrosis of Sin3a-LOF mice but not with AT2 cell ablation and the demonstration that senolytic drugs were protective. Interestingly, a recent publication of a small Phase 1 study in IPF patients using the senolytic agents Dasatinib and Quercetin was performed and although the primary endpoint of change in Iung function was negative, patients reported improvements in breathlessness (94). Our finding that elimination of senescent AT2 cells from lungs of Sin3a-LOF mice protects from progressive fibrosis supports a critical role for AT2 senescence in both initiation and progression of IPF.…”
Section: Discussionsupporting
confidence: 57%
“…The critical role for AT2 senescence in both initiation and progression of fibrosis was suggested by progressive fibrosis of Sin3a-LOF mice but not with AT2 cell ablation and the demonstration that senolytic drugs were protective. Interestingly, a recent publication of a small Phase 1 study in IPF patients using the senolytic agents Dasatinib and Quercetin was performed and although the primary endpoint of change in Iung function was negative, patients reported improvements in breathlessness (94). Our finding that elimination of senescent AT2 cells from lungs of Sin3a-LOF mice protects from progressive fibrosis supports a critical role for AT2 senescence in both initiation and progression of IPF.…”
Section: Discussionsupporting
confidence: 57%
“…Accumulation of senescent cells has been implicated in the pathogenesis of organ fibrosis and might be therapeutically targeted using senolytic agents. A recent first‐in‐humans, open‐label trial of senolytic therapy using dasatinib plus quercetin in idiopathic pulmonary fibrosis (IPF) showed that functional clinical improvement was associated with reduced levels of circulating proteins, microRNAs, and cytokines related to senescence‐associated secretory phenotype (SASP) . Similarly to IPF, systemic sclerosis (SSc) is commonly complicated by fibrotic interstitial lung disease (ILD) and presently lacks approved therapies.…”
mentioning
confidence: 99%
“…Senolytic compounds are being developed to treat numerous age-related diseases including arthritis, cardiovascular and Alzheimer's disease [53,54]. Clinical studies testing senolytics in idiopathic pulmonary fibrosis are already showing efficacy and more clinical studies are ongoing [55,56]. The SASP secreted by SnCs include cytokines associated with a TH17 immune response including IL6, IL1β, and the loss of SnCs in the IL17 knockout models further supports the IL17-SnC connection.…”
Section: Discussionmentioning
confidence: 91%